Development Of Conventional Savings And Loan Business Activities Into Sharia Savings And Loan Business Activities - Sova, Mohamad Sofan; Firdaus, Achmad; Mulyana, Rahmat (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Seeing the potential of the Muslim majority in this country and the euphoria of desire from the leader in the region to apply the Sharia economic principle. However, it is not by the quantity of the successful conversion of the conventional Savings and Loans Business Cooperatives into Sharia Saving and Financing Cooperatives. This research aims to identify problems, formulate solutions, and design strategies for converting conventional Savings and Loans Business Cooperatives into Sharia Saving and Financing Cooperatives. This research uses the Analytic Network Process (ANP) method by collecting opinions from various experts, such as practitioners, regulators, and experts in converting conventional Savings and loan cooperatives into Sharia Savings and loan cooperatives. This research discovers that there were similar opinions on the problems, that internal aspects caused the low conversion rate. Stakeholder interests and human resource needs are the dominant internal problems influencing the most. To solve this problem by processing data from all the respondents based on average results, the priority is the aspect of education and communication. The second priority is the aspect of gradual conversion. The proposed solution will be more effective using a market-driven strategy and rational persuasion. The implication is that the government and other stakeholders can promote the education and communication sector, where education in the form of internships and DPS or Sharia Economics training will have a significant impact.